Mitochondrial Sirtuins and Their Relationships with Metabolic Disease and Cancer - Kumar, Surinder (Antioxid Redox Signal, 2015)
Significance: Maintenance of metabolic homeostasis is critical for cellular and organismal health. Proper regulation of mitochondrial functions represents a crucial element of overall metabolic homeostasis. Mitochondrial sirtuins (SIRT3, SIRT4, and SIRT5) play pivotal roles in promoting this homeostasis by regulating numerous aspects of mitochondrial metabolism in response to environmental stressors. Recent Advances: New work has illuminated multiple links between mitochondrial sirtuins and cancer. SIRT5 has been shown to regulate the recently described post-translational modifications succinyl-lysine, malonyl-lysine, and glutaryl-lysine. An understanding of these modifications is still in its infancy. Enumeration of SIRT3 and SIRT5 targets via advanced proteomic techniques promises to dramatically enhance insight into functions of these proteins. Critical Issues: In this review, we highlight the roles of mitochondrial sirtuins and their targets in cellular and organismal metabolic homeostasis. Furthermore, we discuss emerging roles for mitochondrial sirtuins in suppressing and/or promoting tumorigenesis, depending on the cellular and molecular context. Future Directions: Currently, hundreds of potential SIRT3 and SIRT5 molecular targets have been identified in proteomic experiments. Future studies will need to validate the major targets of these enzymes, and elucidate how acetylation and/or acylation modulate their functionality. A great deal of interest exists in targeting sirtuins pharmacologically; this endeavor will require development of sirtuin-specific modulators (activators and inhibitors) as potential treatments for cancer and metabolic disease. Antioxid. Redox Signal. 22, 1060–1077.